On Some Applications of the Maximum Principles to a Variety of Elliptic and Parabolic Problems - Samuel, Sajan K. (2019)
A Master of Science thesis in Mathematics by Sajan K. Samuel entitled, “On Some Applications of the Maximum Principles to a Variety of Elliptic and Parabolic Problems”, submitted in July 2019. Thesis advisor is Dr. Cristian Enache. Soft and hard copy available.